Employability Skills and Career Development Self-Efficacy as Indicators for Workforce Success - Omar, Muhd Khaizer; Wan Muhamad, Wan Munzareen; Ismail, Normala; Zakaria, Anis; Mohd Kadir, Khairunisa (Journal of Technical Education and Training, 2023)
The development of graduates’ employability skills has become one of crucial agenda in today’s educational milieu. One if the strategies is my adding the soft skills components in teaching and learning delivery across curriculum. This agenda includes Technical and Vocational and Education and Training (TVET) academic program which now has become the forefront agenda to spearhead the local skilled workforce for the nation. The research employed a quantitative descriptive and cross-sectional study among vocational college students from diploma programs across field of studies to combat numerous issues related to graduates’ preparedness on entering workforce, particularly on lack of employability skills. The employability skills section of the instrument was adapted from Grant, Malloy, and Murphy (2009) and Sarigoz (2012). The CD-SEI (Career Development Self-Efficacy Inventory) was replicated from Yuen et al. (2005) as dependent variable. Findings related to employability skills were indicated at a moderate level. The self-efficacy for career development was moderately high. Students’ self-efficacy for career development was not significantly influenced by the demographic variables of gender or academic success. Additionally, the results indicated that vocational college students have higher cognitive skills which significantly predicted the career development self-efficacy. The results of this study can be capitalized as guidelines to carry out a curriculum that is more industrially driven, contributing the exposure to industrial experiences as self-efficacy and employability skills values before venturing job market.